Enhancing Competitiveness of OTOP Entrepreneurs in Narathiwat Province - Sumalee Grodgangunt (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
OTOP is a product that is promoted to provide grassroots people the ability to become household-level entrepreneurs, thereby increasing the value of the household economy. Therefore, the objectives of this research were: 1) to analyze a causal relationship of government policy on OTOP promotion, market readiness of entrepreneurs, and enhancing the competitiveness of OTOP entrepreneurs in Narathiwat Province, 2) to analyze enhancing the competitiveness of OTOP entrepreneurs in Narathiwat Province. The sample group consisted of 240 members. The results revealed that 1) causal relationship is consistent with the empirical data. A chi-square = 16.44 and a P-Value = 0.17, indicating that the causal relationship model was consistent with the empirical data when considering various measurement indices. CFI = 1.00, GFI = 0.99, AGFI = 0.90, RMR = 0.005, RMSEA = 0.04 and CN = 365.52. 2) Enhancing the competitiveness of OTOP entrepreneurs in Narathiwat Province (COMPETE) has obtained total effect from the government policy on OTOP (POLICY) that affect positively of 0.21 by a total indirect effect. Enhancing competitiveness (COMPETE) is obtained total effect from the entrepreneur’s market readiness (READY) positively of 0.60 by an overall direct effect. Entrepreneur’s market readiness (READY) has gained total effect from government policy on OTOP (POLICY) that has a positive effect of 0.70 by direct effect. It disclosed that the enhancing competitiveness of OTOP entrepreneurs derives from 2 factors: market readiness of entrepreneurs and government policy on OTOP promotion, due to both are very high relations at 70 percent.